Analisis Pajak Daerah Dan Retribusi Daerah Terhadap Pertumbuhan Ekonomi Melalui Pendapatan Asli Daerah di Kabupaten Malang - Muhamad Mukhlis (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study investigates the influence of regional taxes and levies on economic growth, with locally-generated revenue serving as a mediating variable in Malang Regency from 2018 to 2023. The research follows a quantitative design, utilizing secondary data obtained through documentation. A saturated sampling technique was applied to select the sample, and the data was processed using SmartPLS 3.0. The findings reveal that regional taxes and levies do not directly impact economic growth. However, both taxes and levies play a significant role in increasing locally-generated revenue, which, in turn, enhances economic growth. Nevertheless, locally-generated revenue does not mediate the effect of regional taxes and levies on economic growth.